Gastrointestinal coronavirus disease 2019: epidemiology, clinical features, pathogenesis, prevention, and management. (2nd January 2021) - Deidda, Simona; Tora, Lorena; Firinu, Davide; Del Giacco, Stefano; Campagna, Marcello; Meloni, Federico; Orrù, Germano; Chessa, Luchino; Carta, Mauro Giovanni; Melis, Alessandra; Spolverato, Gaya; Littera, Roberto; et al.
ABSTRACT: Introduction: The new Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the etiologic agent of coronavirus disease 2019. Some authors reported pieces of evidence that patients with SARS-CoV-2 infection could have direct involvement of the gastrointestinal tract, and in symptomatic cases, gastrointestinal symptoms (diarrhea, nausea/vomiting, abdominal pain) could be very common. Area covered: In this article, we reviewed current-published data of the gastrointestinal aspects involved in SARS-CoV-2 infection, including prevalence and incidence of specific symptoms, the presumptive biological mechanism of GI infection, prognosis, clinical management, and public health-related concerns on the possible risk of oral-fecal transmission. Expert opinion: Different clues point to direct virus infection and replication in mucosal cells of the gastrointestinal tract. In vitro studies showed that SARS-CoV-2 could enter into the gastrointestinal epithelial cells by the Angiotensin-Converting enzyme two membrane receptor. These findings, coupled with the identification of viral RNA found in stools of patients, clearly suggest that direct involvement of the gastrointestinal tract is very likely. This can justify most of the gastrointestinal symptoms but also suggest a risk for an oral-fecal route for transmission, additionally or alternatively to the main respiratory route.